Potential antitumor properties of a protein isolate obtained from the seeds of Amaranthus mantegazzianus - Barrio, Daniel Alejandro (2010)
Background: Amaranth is a crop that can be grown in different soils and climates, being resistant to high temperatures, drought, and some pests. The amaranth plant has nutritional qualities and desirable biological properties. Aim of the study The aim of the study is to investigate the potential antitumor properties of Amaranthus-mantegazzianus-protein isolate (MPI) and to elucidate the possible mechanism of action. Methods: We use four different tumor-derived and in vitro-transformed cell lines with different morphology and tumorigenicity (MC3T3E1, UMR106, Caco-2, and TC7). Results: The MPI showed an antiproliferative effect on four cell lines with different potencies. The tumor-cell line UMR106 was the most sensitive (IC50: 1 mg/ml). This antiproliferative effect of the MPI was enhanced by protease treatment (IC50: 0.5 after 30% hydrolysis). In addition, the MPI produced morphological changes and caused a rearrangement of the cytoskeleton in UMR106 cell line. In an attempt to elucidate the mechanism of action, we observed that the MPI inhibited cell adhesion and induced apoptosis and necrosis in the UMR106 cell line. In reversibility studies, we were able to observe both temporary and permanent cytostatic and cytotoxic effects on the part of the MPI, depending on its concentration. Conclusions: we report a protein isolate from the seeds of Amaranthus mantegazzianus that exhibit potential antitumor properties and propose a putative mechanism of action.